2022
DOI: 10.3389/fendo.2022.1060187
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish endochondral growth zones as they relate to human bone size, shape and disease

Abstract: Research on the genetic mechanisms underlying human skeletal development and disease have largely relied on studies in mice. However, recently the zebrafish has emerged as a popular model for skeletal research. Despite anatomical differences such as a lack of long bones in their limbs and no hematopoietic bone marrow, both the cell types in cartilage and bone as well as the genetic pathways that regulate their development are remarkably conserved between teleost fish and humans. Here we review recent studies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 118 publications
(169 reference statements)
1
6
0
Order By: Relevance
“…Other than in MCDS, where structural deformities occur in endochondral bones, we expected deformities in both bone and cartilage in col10a1 Δ633a medaka mutants. In line with this, we showed that the ceratohyal bone, which in teleost fish develops via endochondral ossification, 57 was shorter in WT/m col10a1 Δ633a medaka mutants. In addition, cartilaginous structures such as the ceratobranchials and gill filaments were severely deformed in the medaka mutants.…”
Section: Discussionsupporting
confidence: 82%
“…Other than in MCDS, where structural deformities occur in endochondral bones, we expected deformities in both bone and cartilage in col10a1 Δ633a medaka mutants. In line with this, we showed that the ceratohyal bone, which in teleost fish develops via endochondral ossification, 57 was shorter in WT/m col10a1 Δ633a medaka mutants. In addition, cartilaginous structures such as the ceratobranchials and gill filaments were severely deformed in the medaka mutants.…”
Section: Discussionsupporting
confidence: 82%
“…Each of these genes was upregulated in our study in pelagic foraging MZ compared with benthic foraging conspecifics. Given the well-studied roles for cell proliferation in bone formation, shape and growth (Capecchi et al, 2018;Du et al, 2021;Gao et al, 2020;Le Pabic et al, 2022;Shekhar et al, 2019), the data presented here suggest that this mechanism is important in mediating skeletal plasticity in this species.…”
Section: Differential Gene Expression Is Rare Between Foraging Enviro...mentioning
confidence: 66%
“…Compared to humans, in zebrafish limited skeletal structures undergo endochondral ossification, whereas a majority of the human skeleton undergoes this process, which could explain some of the differences in efemp1 phenotypes between fish and humans. One location where endochondral ossification occurs in both humans and zebrafish are in the skull and pharyngeal skeleton in the cranium, respectively, which could be why we see changes in craniofacial morphology in both human and zebrafish (Le Pabic et al 2022). Work understanding the potential perturbation of EFEMP1 and ECM1 interaction could broaden our understanding of the skeletal phenotypes in our models and in individuals with EFEMP1 variants.…”
Section: Discussionmentioning
confidence: 95%